Treating Methamphetamine-Induced Resistant Psychosis with Clozapine - Seddigh, Ruohollah; keshavarz-Akhlaghi, Amir-Abbas; Shariati, Behnam (Case Reports in Psychiatry, 2014)
Background. Methamphetamine-induced psychosis (MIP) in Iran has turned into a serious issue in terms of health and treatment, lacking any obvious treatment methods for its resistant cases. Aims of Case Report. In the present study, a number of two cases of treatment of MIP with clozapine, which were resistant to the treatment with other antipsychotics, have been reported. Both cases completely responded to the treatment in only 2 weeks and no signs of psychosis relapse were seen in an 8-9 follow-up. Conclusion. Because of its particular pharmacologic features, clozapine may be effective in treating MIP.